## Monday, May 20, 2013

### 60-01 Basics of Quadratic Equations (Grades 9 to 12) Part-01

Blog-60

Dear Students,

Download following files for learning Formulas more effectively. Take the print out of these files and write your answers daily to improve your scores in 10th standard/grade.

[ Note: The following 2 files are available in the secured drive. While downloading, your email might be asked. Please provide it to download the files. I assure that your email-id will not be given to anybody ]

Following two files are very important to improve your base for remembering the formulas. It is 100 % free for all the students of the world. Download these two files, take the Print Out of these files on two sides of the paper and practice these formulas for your benefit to get high scores in Mathematics Standard 10/ Grade 10.

Please send the request for downloading the following files which will really help you to improve your mathematical skills for Standard 10 / Grade 10. This is the PRACTICE SHEET of Formulas.

An equation of the form a x 2 + b x + c = 0 where a, b, and c are the real numbers and a ≠ 0 is known as an quadratic equation. Here "x" is the variable. The highest power of variable x is 2 so it is an equation of order 2. That's why it is known as quadratic equation. Here "a" is the coefficient of  2, "b" is the coefficient of  x, and "c" is the constant term of the quadratic equation.

Roots of the quadratic equation:
The values of the variable "x" which satisfy the equation are known as the roots of the equation. For the quadratic equation, we have two roots. To understand the concept of the roots, let see the following case which is taken in the reverse direction.

Let us take the roots of the quadratic equation as x = 2 and x = 3.

x = 2    so (x  - 2) = 0
x = 3    so (x  - 3) = 0.
so taking the product of these two brackets we have,
(x - 2) (x  - 3) = 0
x 2 - 2 x - 3 x + 6 = 0
x 2 - 5 x + 6 = 0
So, 2 - 5 x + 6 = 0 is the quadratic equation in "x" which has two roots as 2 and 3.

Now we will study few examples on roots of the quadratic equation.

1] Check whether the values given against the quadratic equation are the roots of the equation or not.

a]  3 x 2 + 7 x + 2 = 0,     -1, -2, -1/3, and -3.

Solution:
1)   Let us take, L H S  =   3 x 2 + 7 x + 2
2)   We need to check whether -1, -2, -1/3, and -3 are the roots of 3 x 2 + 7 x + 2 = 0 or not,
3)   so put x = - 1 in L H S , we get,
L H S  =  3 x 2 + 7 x + 2
L H S  =  3 (-1) 2 + 7 (-1) + 2
L H S  =  3 (1) - 7  + 2
L H S  =  3  - 7  + 2
L H S  =  5  - 7
L H S  =  - 2  ≠ 0
L H S  ≠ R H S.
So, -1 is not a root of the quadratic equation 3 x 2 + 7 x + 2 = 0.

4)   so put x = - 2 in L H S , we get,
L H S  =  3 x 2 + 7 x + 2
L H S  =  3 (-2) 2 + 7 (-2) + 2
L H S  =  3 (4) - 14  + 2
L H S  =  12  - 14  + 2
L H S  =  14  - 14
L H S  =  0
L H S  =  R H S.
So, -2 is a root of the quadratic equation 3 x 2 + 7 x + 2 = 0.

5)   so put x = - 1/3 in L H S , we get,
L H S  =  3 x 2 + 7 x + 2
L H S  =  3 (-1/3) 2 + 7 (-1/3) + 2
L H S  =  3 (1/9) - 7/3  + 2
L H S  =  3/9  - 7/3  + 2
L H S  =  1/3  - 7/3  + 2
L H S  =  (1 - 7)/3  + 2
L H S  =  - 6/3  + 2
L H S  =  - 2  + 2
L H S  =  0
L H S  =  R H S.
So, -1/3 is a root of the quadratic equation 3 x 2 + 7 x + 2 = 0.

6)   so put x = - 3 in L H S , we get,
L H S  =  3 x 2 + 7 x + 2
L H S  =  3 (-3) 2 + 7 (-3) + 2
L H S  =  3 (9) - 21  + 2
L H S  =  27  - 21  + 2
L H S  =  6  + 2
L H S  =  8  ≠ 0
L H S  ≠ R H S.
So, -3 is not a root of the quadratic equation 3 x 2 + 7 x + 2 = 0.

b]   x 2 - 6 x + 7 = 0,     2, -2, and (3 2).
Solution:
1)   Let us take, L H S  =   x 2 - 6 x + 7
2)   We need to check whether 2, -2, and (3 2) are the roots of 2 - 6 x + 7 = 0 or not,
3)   so put x = 2 in L H S , we get,
L H S  =  2 - 6 x + 7
L H S  =  (2) 2 - 6 (2) + 7
L H S  =  4  - 12  + 7
L H S  =  - 8  + 7
L H S  =  - 1
L H S  =  - 1  ≠ 0
L H S  ≠ R H S.
So, 2 is not a root of the quadratic equation 2 - 6 x + 7 = 0

4)   so put x = - 2 in L H S , we get,
L H S  =  2 - 6 x + 7
L H S  =  (- 2) 2 - 6 (- 2) + 7
L H S  =  4  + 12  + 7
L H S  =  16  + 7
L H S  =  23
L H S  =  23  ≠ 0
L H S  ≠ R H S.
So, - 2 is not a root of the quadratic equation 2 - 6 x + 7 = 0

5)   so put x = (3 2) in L H S , we get,
L H S  =  2 - 6 x + 7
L H S  =  (3 2) 2 - 6 (3 2) + 7
L H S  =  (9 + 62 + 2)  - 18 - 62 + 7
L H S  =  11 + 6  - 18 - 62 + 7
L H S  =  18 + 6  - 18 - 62
L H S  =  0
L H S  =  R H S.
So, (3 2) is a root of the quadratic equation 2 - 6 x + 7 = 0

Next part of this topic will be published in the next Blog.

Anil Satpute